Head injury at early ages is associated with risk of Parkinson's disease. (February 2016) - Taylor, Kathryn M.; Saint-Hilaire, Marie-Helene; Sudarsky, Lewis; Simon, David K.; Hersh, Bonnie; Sparrow, David; Hu, Howard; Weisskopf, Marc G.
Abstract: Introduction: The literature on the effect of head injuries on the risk of PD is inconclusive. Some researchers have hypothesized that studies that have seen an effect are simply capturing injury related to pre-clinical PD. However in animal models brain inflammation, which can be initiated by head trauma, has been shown to produce PD-like effects. Furthermore, animal studies have found that early life inflammation in particular is of relevance for PD pathology. Methods: We conducted an unmatched case–control study of 379 neurologist confirmed PD patients and 230 controls from the greater Boston, Massachusetts area with questionnaire data on history of head injury and other covariates. We used multivariable logistic regression to estimate adjusted odds ratios (OR) and their corresponding 95% confidence intervals (CI) for PD. Results: When we excluded injuries that occurred less than 10 years prior to the diagnosis of PD (in order to avoid reverse causation), we found an increased risk of PD associated with a head injury that resulted in a loss of consciousness, but it did not reach statistical significance (OR = 1.57; 95% CI = 0.89–2.80). We found a significant (p = 0.04) effect of age at first head injury. For every 5 year earlier age at first head injury with loss of consciousness the OR for PD was 1.37 (95% CI: 1.01–1.86). Conclusion: Our results suggest that head injury in early life increases the risk of PD. Highlights: Brain inflammation in animals in early life is linked with increased PD-like pathology. Head injury is a known cause of brain inflammation. The association between head injury and an increase in the risk of PD is debated. Robust methodology shows an increased risk of PD with head injuries in early childhood. This could explain inconsistencies in the association between head injury and PD.